Clinical Characteristics and Outcomes Based on Race of Hospitalized Patients With COVID-19 in a New Orleans Cohort. (13th August 2020) - Silver, Victoria; Chapple, Andrew G; Feibus, Allison H; Beckford, Jeremy; Halapin, Natalie A; Barua, Delphi; Gordon, Angellica; Baumgartner, Will; Vignes, Seth; Clark, Cullen; Kamboj, Sanjay; Lim, Stephen C; et al.
Abstract: Background: In Louisiana, deaths related to COVID-19 have disproportionately occurred in Black persons. Granular data are needed to better understand inequities and develop prevention strategies to mitigate further impact on Black communities. Methods: We conducted a retrospective study of patients admitted to an urban safety net hospital in New Orleans, Louisiana, with reactive SARS-CoV-2 testing from March 9 to 31, 2020. Clinical characteristics of Black and other racial/ethnic group patients were compared using Wilcoxon rank-sum test and Fisher exact tests. The relationship between race and outcome was assessed using day 14 status on an ordinal scale. Results: This study included 249 patients. The median age was 59, 44% were male, and 86% were age ≥65 years or had ≥1 comorbidity. Overall, 87% were Black, relative to 55% Black patients typically hospitalized at our center. Black patients had longer symptom duration at presentation (6.41 vs 5.88 days; P  = .05) and were more likely to have asthma ( P  = .008) but less likely to have dementia ( P  = .002). There were no racial differences in initial respiratory status or laboratory values except for higher lactate dehydrogenase in Black patients. Patient age and initial oxygen requirement, but not race (adjusted proportional odds ratio, 0.92; 95% CI, 0.70–1.20), were associated with worse day 14 outcomes. Conclusions: Our results demonstrate minor racial differences in comorbidities or disease severity at presentation, and day 14 outcomes were not different between groups. However, Black patients were disproportionately represented in hospitalizations, suggesting that prevention efforts should include strategies to limit SARS-CoV-2 exposures and transmission in Black communities as one step toward reducing COVID-19-related racial inequities.